Mangrove consortium resistant to the emerging contaminant DEHP: Composition, diversity, and ecological function of bacteria. - Julia de Morais Farias; Leandro Araujo Argolo; Raquel A F Neves; Natascha Krepsky; José Augusto P Bitencourt (PLoS ONE)
The continuous use of Di(2-ethylhexyl) phthalate (DEHP) in plastic products turns it into a ubiquitous contaminant in the environment. However, DEHP can cause harm to human beings, wildlife, and ecosystems due to its estrogenicity and toxicity. Thus, finding an efficient approach to removing this contaminant from the environment is crucial. The present study aimed to prospect and characterize a bacterial consortium (MP001) isolated from a neotropical mangrove for DEHP bioremediation. A laboratory experiment was performed with environmentally relevant DEHP concentrations (0.05, 0.09, 0.19, 0.38, 0.75, 1.50, 3.00, and 6.00 mg L-1) to determine the consortium resistance to this contaminant and high-throughput sequencing was accomplished to assess the bacterial composition, diversity, and potential ecological function of consortium MP001. The consortium MP001 presented a significant biomass increase throughout short-term incubations with increasing concentrations of DEHP (GLMs, p< 0.001). MP001 was constituted by Paraclostridium sp. (78.99%) and Bacillus sp. (10.73%). After 48 h of consortia exposure to DEHP, the bacterial population changed to Paraclostridium (50.00%), Staphylococcus sp. (12.72%), Staphylococcus epidermidis (10.40%) and Bacillus sp. (17.63%). In the negative control, the bacteria community was composed of Paraclostridium sp. (54.02%), Pseudomonas stutzeri (19.44%), and Staphylococcus sp. (11.97%). The alpha diversity of the MP001 consortium was not significant (Kruskall-Wallis; p > 0.05), and no significant difference was found between the DEHP treatment and the negative control. Furthermore, the potential ecological function found in the consortium MP001 with higher potential for application in bioremediation purposes was fermentation. The results found in this study highlight the potential of a bacterial consortium to be used in the bioremediation of DEHP-contaminated aquatic environments.